First Detection and Genetic Characterization of New Equine Parvovirus Species Circulating among Horses in Korea - Jungho Yoon; Taemook Park; Ahram Kim; Heeeun Song; Byung-Joo Park; Hee-Seop Ahn; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; et al. (Veterinary Sciences, 2021)
Equine parvovirus-cerebrospinal fluid (EqPV-CSF) and eqcopivirus (EqCoPV) are new parvovirus species (EqPVs) identified from various tissues (CSF, blood, and respiratory swabs) in horses with neurologic and respiratory diseases. In this study, we described the prevalence rate of EqPV-CSF and EqCoPV in 133 and 77 serum and fecal samples, respectively, using polymerase chain reaction. Further, we analyzed the potential risk factors for infection. We calculated the nucleotide and amino acid similarity and constructed phylogenetic trees. There was a moderate-to-high prevalence rate (EqPV-CSF: 3.8%; EqCoPV 9.8%) of each virus in serum; moreover, age, country of foaling, and clinical colic signs were significantly associated with the EqPVs infection. The newly identified EqPV-CSF/EqCoPV genomes had high nucleotide and amino acid identities with previously isolated strains in the USA. In phylogenetic analysis, they clustered and formed a new subgroup in the genus Copiparvovirus. To our knowledge, this is the first field epidemiologic study on EqPV-CSF and EqCoPV using both serum and fecal samples. Our findings demonstrate the risk factors for infection and could facilitate the development of disease prevention strategies.